RANCANGAN MONITOR AIR CONDITIONER SECARA TERPUSAT MENGGUNAKAN MIKROKONTROLLER DI BARAK CURUG 1 SEKOLAH TINGGI PENERBANGAN INDONESIA - Alghani; Suse Lamtiar S (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
With the draft is expected to be used as the operating system of centeralized airconditioning Split. Based on the existing conditions in the dormitory Curug 1 often the negligence of cadets when leaving the dormitory in the state of air conditioning is still operating. To make it easier to monitor the AC work system when cadets leave the dormitory, the writer tries to make a simple design of this, but does not reduce the functionality of the existing equipment. To monitor and operate AC the writer intends to create a design that can monitor and control AC centrally using a microcontroller as a controller and the computer through Visual Studio as the monitoring interface put on BIMTAR and duty cadets as operators. Thus this design